Kajian Literatur: Penggunaan Frase Instruksional dalam Pembelajaran Bilingual di Sekolah Dasar - Cahyaningrum, Aulia Dwi; Ristiani, Rima; Adilia, Tsabita Daffa; Tanjung, Nurul Widya; Maulana, Fahrizal Husni; Firliani, Atikah Abel; Widagdo, Arif (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the use of instructional phrases in bilingual learning at the elementary school level. Using a literature study method and a descriptive qualitative approach, this study examines various relevant literature and previous research results. The results of the study indicate that instructional phrases have an important role in creating a conducive bilingual learning environment, building meaningful interactions, and supporting students' academic understanding. Phrases such as class commands, task instructions, feedback, and activity transitions have been shown to make it easier for students to understand the context of bilingual learning. The challenges in its implementation are the limited competence of teachers in English, the diversity of students' language abilities, and the need for differentiation strategies. Therefore, teacher training, the use of linguistic approaches, and strategies such as translanguaging and Total Physical Response (TPR) are the suggested solutions. This study provides theoretical and practical contributions to the development of effective bilingual learning practices in elementary schools.